Bullous pemphigoid: therapeutic algorithm and practical management. (July 2013) - Daniel, Benjamin S; Murrell, Dedee F; Borradori, Luca
<x xml:space="preserve">Abstract</x> Introduction: Bullous pemphigoid (BP) is the most common autoimmune subepidermal blistering disease of the skin and mucosae. BP typically affects the elderly and manifests with severe itch, localised or generalised eczematous, urticated and/or bullous lesions. Its morbidity and impact on the quality of life are important. The disease is significantly associated with neurological disorders, such as stroke, Parkinson disease, major cognitive impairment and multiple sclerosis. Diagnosis of BP critically relies on immunopathologic examinations, particularly direct immunofluorescence microscopy studies. Areas covered: This paper looks at the evidence of therapies commonly used in bullous pemphigoid. Expert opinion: Treatment of BP has been a challenge, given the relative rarity of the disease, lack of good quality randomised controlled trials, the presence of co-morbidities in the affected elderly population and the high mortality rate. Recent controlled studies have indicated that potent topical corticosteroids constitute a more effective therapy for BP when compared to oral corticosteroids in terms of control of the disease, side effect profile and overall survival. Other therapies have been employed with varying success, but are not validated yet. Improved knowledge of the pathophysiology of BP will hopefully allow the development of new immunomodulatory treatments for this debilitating disease.